2020
DOI: 10.1101/2020.11.03.367391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of Antibody Immunity to SARS-CoV-2

Abstract: SARS-CoV-2 has infected 47 million individuals and is responsible for over 1.2 million deaths to date. Infection is associated with development of variable levels of antibodies with neutralizing activity that can protect against infection in animal models. Antibody levels decrease with time, but the nature and quality of the memory B cells that would be called upon to produce antibodies upon re-infection has not been examined. Here we report on the humoral memory response in a cohort of 87 individuals assessed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
221
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(259 citation statements)
references
References 65 publications
(128 reference statements)
34
221
0
3
Order By: Relevance
“…However, our findings support the hypothesis of Gaebler et al, who suggested that the accumulation of IgG somatic mutations-and subsequent production of antibodies with increased neutralizing potency-allow the maintenance of neutralizing activity levels, despite the decline in specific antibody titers 5 . Of note, our follow-up period encompassed two waves of the COVID-19 outbreak in our country.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…However, our findings support the hypothesis of Gaebler et al, who suggested that the accumulation of IgG somatic mutations-and subsequent production of antibodies with increased neutralizing potency-allow the maintenance of neutralizing activity levels, despite the decline in specific antibody titers 5 . Of note, our follow-up period encompassed two waves of the COVID-19 outbreak in our country.…”
supporting
confidence: 91%
“…For the latter analysis, linear mixed-effect models with random intercepts and slopes were used, and different breakpoints were tested; the one with the best adjustment was chosen. For the longitudinal analysis of neutralizing activity, patients were grouped into two severity groups according to the WHO progression scale as proposed elsewhere 21 : asymptomatic or mild (levels 1-3), and hospitalized (levels [4][5][6][7][8][9][10]. Differences between the two severity groups were assessed using the likelihood ratio Figure 1a; Mann-Whitney test for comparative analysis) and modeled data as dotted lines (likelihood ratio test for comparative analysis).…”
Section: Resultsmentioning
confidence: 99%
“…The model's initial conditions are set to approximate current US disease prevalence and seroprevalence (as of November 2020): ( = 0) = 0.2 % ( = 0) = 8% (34) Our model lacks a seasonal component for SARS-CoV-2 transmission, as such associations have been conjectured (35) but not proven, and it also assumes a 18-month duration of natural immunity, as an optimistic estimate based on the duration of antibody responses seen so far months (20)(21)(22). The disease-preventing interventions and return to normalcy (which would correspond to a return to the pre-pandemic R0 of 5.7) are assumed to occur at the beginning of the simulation interval.…”
Section: Seirs Modelmentioning
confidence: 99%
“…If immunity to SARS-CoV-2 by natural infection is not life-long, as suggested by many studies (20)(21)(22), and if effective interventions are not undertaken at a large scale, the virus will become endemic. As shown in Figure 4, this means that in the long term, SARS-CoV-2 will reach a steady-state prevalence in the population.…”
Section: If Covid-19 Becomes Endemic Steady-state Yearly Spread Depementioning
confidence: 99%
See 1 more Smart Citation